Consumption of food after removal of tounge - case study - Hamerlińska, Agnieszka; Gniezdzia – Buc, Izabela (Journal of Education, Health and Sport, 2017)
Tounge removals are most likely to occur as a result of cancer. Consequence of organ loss is many. After the resection changes the ability to eat food. This article deals with the description of the swallowing process and its disorders. The content is cancer.